Ethical procedures and patient consent differ in Europe. Issue 2 (February 2015) - Stamer, Ulrike M.; Naef, Nadja; Porz, Rouven; Stuber, Frank; Leva, Brigitte; Meissner, Winfried; Fletcher, Dominique
<x xml:space="preserve">Abstract</x> BACKGROUND Research ethics approvals, procedures and requirements for institutional research ethics committees vary considerably by country and by type of organisation. OBJECTIVE To evaluate the requirements and procedures of research ethics committees, details of patient information and informed consent based on a multicentre European trial. DESIGN Survey of European hospitals participating in the prospective observational study on chronic postsurgical pain (euCPSP) using electronic questionnaires. SETTING Twenty-four hospitals in 11 European countries. PARTICIPANTS From the 24 hospitals, 23 local investigators responded; 23 answers were analysed. OUTCOME MEASURES Comparison of research ethics procedures and committee requirements from the perspective of clinical researchers. Comparison of the institutions' procedures regarding patient information and consent. Description of further details such as costs and the duration of the approval process. RESULTS The approval process lasted from less than 2 weeks up to more than 2 months with financial fees varying between 0 and 575 [Euro sign]. In 20 hospitals, a patient information sheet of variable length (half page up to two pages) was provided. Requirements for patients' informed consent differed. Written informed consent was mandatory at 12, oral at 10 and no form of consent at one hospital. Details such as enough time for consideration, possibility for withdrawal and risks/benefits of participation were provided in 25 to 30% of the institutions. CONCLUSION There is a considerable variation in the administrative requirements for approval procedures by research ethics committees in Europe. This results in variation of the extent of information and consent procedures for the patients involved. TRIAL REGISTRATION euCPSP in Clinicaltrials.gov identifier: NCT01467102; PAIN-OUT in Clinicaltrials.gov identifier: NCT02083835.